(untitled) (Communication & Society, 2023)
Plebiscites, secession consultations, and referendums are electoral processes that are different from conventional voting. Conversations before these types of elections tend to focus on very different aspects than those generated during the election of an authority or public office, with a focus on the future impacts that each decision may have on a country, generally taking one side or the other. In the current media ecosystem, this conversation takes place largely on social platforms and networks, where users consume content and interact with it, becoming active prosumer audiences. The aim of this research is to determine what elements determine this type of discourse on TikTok –as a social network that is trending among digital communities–, what type of profiles promote them, and what narrative code is used. To this end, based on the case of the referendum planned in Scotland for 2023, an exploratory quantitative and qualitative study is proposed based on the publications discriminated by hashtags related to the topic through an analysis carried out in an application called PyCharm (Python) TikTok Research. The results suggest that on TikTok this type of content has a large reach, but it is not possible to determine precisely whether it has a specific effect or impact. However, the rate of user engagement and interaction with this content opens the possibility of eventually greater influence than on other platforms.